Characterization of the physicochemical, thermal and rheological properties of cashew kernel starch - Chen, Nan (2022)
The study aimed to characterize physicochemical, thermal, and rheological properties of cashew nut starch (CNS) and then compare the obtained results with the properties of potato and corn starches. CNS showed higher gelatinization temperatures (112.29 °C) than those noted for potato and maize starches (78.44–94.65 °C). In addition, CNS had higher peak viscosity (19.03 mPa·s) than high amylose corn starch. The static shear rheological test indicated that the CNS followed a pseudoplastic behavior. In addition, CNS sample showed a thixotropic patter, which was less pronounced than that observed for potato starch, but higher than the value reported for high amylose corn starch. These results demonstrated that the shear resistance of CNS was lower than high amylose corn starch, but higher than potato starch. The storage and loss modulus (G' and G“, respectively) of the CNS were higher than those reported for the rest of samples. In this line, elastic properties were predominant in CNS sample. In conclusion, results from this study provided insight into physicochemical and structural properties of cashew nut starch, which could represent a preliminary step for its future application in food processing.